2015
DOI: 10.1681/asn.2014050508
|View full text |Cite
|
Sign up to set email alerts
|

Renal Glycosphingolipid Metabolism Is Dysfunctional in Lupus Nephritis

Abstract: Nearly one half of patients with lupus develop glomerulonephritis (GN), which often leads to renal failure. Although nephritis is diagnosed by the presence of proteinuria, the pathology of nephritis can fall into one of five classes defined by different forms of tissue injury, and the mechanisms involved in pathogenesis are not completely understood. Glycosphingolipids are abundant in the kidney, have roles in many cellular functions, and were shown to be involved in other renal diseases. Here, we show dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
94
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(107 citation statements)
references
References 42 publications
12
94
1
Order By: Relevance
“…1C). As we previously reported in lupus nephritis (41), GSLs in db/db mice were elevated at least in part in the glomeruli. We have recently reported that GSL levels in hematopoietic and leukemia cells are in part determined by glucose availability (47).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…1C). As we previously reported in lupus nephritis (41), GSLs in db/db mice were elevated at least in part in the glomeruli. We have recently reported that GSL levels in hematopoietic and leukemia cells are in part determined by glucose availability (47).…”
Section: Discussionsupporting
confidence: 79%
“…Levels of GSLs in the urine of diabetic patients were consistent with those observed for other kidney diseases in which GSLs play a role. For example, we recently reported elevated levels of GSLs in the urine of patients with lupus nephritis (41). In addition, levels and activity of the enzyme neuraminidase were also increased in the urine of lupus nephritis patients (41).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The literature indicates that inhibition of glucosylceramide synthesis dampens the inflammatory response (35,63), suggesting that inhibition of glucosylceramide synthesis in cisplatin-induced AKI could also reduce inflammatory pathways. Inflammatory pathways are known to perpetuate cisplatin-induced kidney injury; however, our data suggest that ceramide and/or a lack of its metabolism to a protective glycosphingolipid species play a role in the inflammatory response in cisplatininduced AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Glucosylceramide, has been implicated to play a role in a variety of kidney diseases, such as diabetic nephropathy, lupus nephritis, and polycystic kidney disease, as well as decreased kidney function associated with aging (35)(36)(37)(38). Glucosylceramides have been implicated in regulating pathways involved in the above kidney diseases, including cell death, ER stress, and inflammation (23,39,40).…”
mentioning
confidence: 99%